2015
DOI: 10.1007/s13312-015-0770-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between packed red blood cell transfusion and severe form of necrotizing enterocolitis: A case control study

Abstract: Blood Transfusion associated necrotizing enterocolitis is a severe, mainly surgical form of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…[ 50 ] However, other studies have found an association between number of transfusions and incidence of ROP, BPD, and NEC. [ 48 51 52 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 50 ] However, other studies have found an association between number of transfusions and incidence of ROP, BPD, and NEC. [ 48 51 52 ]…”
Section: Discussionmentioning
confidence: 99%
“…So far, the etiology of NEC is still multifactorial (7,8). In pathological morphology, decreased perfusion and ischemia of the intestinal wall may cause disruption of the intestinal barrier, which enables bacterial infection and inflammation (9)(10)(11)(12)(13)(14)(15). It is crucial for suspected neonates to receive diagnostics and appropriate treatment as early as possible.…”
Section: ' Introductionmentioning
confidence: 99%
“…The number of infants enrolled in the study was 444. The overall median (IQR) gestational age and birth weight values of the enrolled infants were 29 (27,31) wk and 1112.5 (860-1315) g, respectively. Most of the infants were born in the hospital (401/444, 90%).…”
Section: Resultsmentioning
confidence: 99%